Reflections on Eviatar Shulman's Rethinking the Buddha: Early Buddhist Philosophy as Meditative Perception. (30th December 2018) - Harvey, Peter
Abstract : Reflections on Eviatar Shulman's Rethinking the Buddha: Early Buddhist Philosophy as Meditative Perception